Acetoxy allenoates as emerging synthons in annulation/cycloaddition reactions - Kumara Swamy, K C; Chauhan, Sachin; Sanjeeva Kumar, A (Chemical communications (Cambridge, England), 2025)
In contrast to the normal allenoates (2,3-butadienoates) that undergo phosphine/amine addition generating dipolar-type intermediates, acetoxy allenoates that contain a facile-leaving -OAc group create electrophilic diene-phosphonium/ammonium intermediates rendering the reactivity pattern vastly different in the two cases. This review highlights the fascinating chemistry of acetoxy allenoates and related substrates. The diene-phosphonium/ammonium intermediate thus formed from acetoxy allenoate [substituted 5-acetoxypenta-2,3-dienoate or 2-(acetoxymethyl)buta-2,3-dienoate] participates in a plethora of cycloaddition/annulation reactions with bisnucleophiles generating multifunctional hetero- or homo-cycles in very few steps. Thus the electron-withdrawing effect of the phosphonium as well as carboxylate groups, making the diene-phosphonium/ammonium intermediates quite electrophilic, has been pivotal to the growth and significant interest during the last 10-15 years in this emerging class of substrates as revealed in this article. A comparison of this chemistry with that of (acetoxy)(acyl)allenes and allenyl acetates is also made briefly.